MAN-MACHINE INTERFACE (MMI) CLIENT_SERVER UNTUK PENGATURAN POSISI MOTOR SERVO - Anshori, Yusuf (MEKTEK, 2011)
In the automatic control of the process manufacturing industry contributed greatly due to the dynamicalsystem setup proved to give good performance such as increasing the quality and pace of the productionprocess, reduce production costs and minimize the tedious routine work to be done by humans. MMI (Man-Macchine Interface) is a system consisting of information and communication technology device that servesas a liaison between people and machines that run a complex industrial process. MMI hardware architecturethat is built consisting of client, server, microcontroller, motor drivers and servo drive. Communication thatoccurs is a two-way communication so that the servo motor can be controlled and monitored the movementand position by the server and client